Effect of acute administration of Clenbuterol on athletic performance in horses - Ferraz, Guilherme C.; Teixeira-Neto, Antonio R.; D'Angelis, Flora H. F.; Lacerda-Neto, Jose C.; Quelroz-Neto, Antonio (Elsevier B.V., 2007)
The aim of the study was to determine the effect of clenbuterol on the anaerobic-threshold of horses on a tread-mill with increasing physical stress, measuring heart rate (HR) and blood levels of lactate, glucose, and insulin. Twelve Arabian horses. were submitted to two physical tests separated by a 10-day interval. Clenbuterol (CL) at 0.8 mu g/kg or saline (control-C) was administered intravenously 30 minutes, before the test. The treadmill exercise test consisted of an initial warmup followed by a gradually increasing effort. There was no statistical difference in either V-2 or V-4 (velocity at which plasma lactate concentration reached 4 and 2 mmol/L, respectively) between the two-experimental groups. For the CL group, V-200, V-180, V-160, and V-140 (velocity at which the rate heart is 140, 160, 180, and 200 beats/minute, respectively) decreased significantly. At rest as well as times 4, 6, and 10 minutes, insulin levels were higher in the group that recieved clenbuterol (P < .05). Contrary to what was expected, apparently, there was no improvement in aerobic metabolism in animals when given a therapeutic dose of the bronchodilator. The elevated heart rate observed could have been attributable to the stimulation of cardiac beta(1) adrenoceptors and the increased insulin levels to the stimulation of pancreatic beta(2) receptors.
Keywords: Horse; exercise; Clenbuterol; performance; Insulin